Estudo comparativo de dois leitos filtrantes com porosidades distintas em sistemas de dupla filtração para tratamento de água - Alcantara, Flávio José Vacari de (2010)
This work evaluates the efficiency of two double filtration systems concerning the turbidity removal from supplying water working under limit situation, this is, raw water with 200 uT of turbidity peaks (maximum recommended for this technology) and without intermediate downflushing on the upflow filters. The upflow filter of one of the double filtration systems had 5 layers of gravel, which granularity varied from 2 to 38 mm and had 38% of porosity. The upflow filter of the second double filtration system had a porous material as media, made in PVC (flexible electrical conduit), with only one diameter, 1/2" and with 91% of porosity. The total height of both medias were 1,8 m. The downflow sand filter was the same one in both double filtration systems. Two experiments took place for each media, varying the filtration rate (120, 180 e 240 m³/m².day). The raw water was proceeding from a 60 meters deep well, to which was added a powder of kaolin to promote the desired water turbidity (200 uT). The pH varied between 6,7 and 7,2 and the alkalinity varied from 99,5 to 107,25 mg CaCO3/L. Preliminary jar tests were also made in order to determinate the dosage of chemicals for the coagulation, and the optimum value encountered was 15 mg/L of free Al2O3 and pH of 6,9. The Polyaluminium Chloride was chosen as chemical coagulant. In the experiments with 120 and 180 m³/m².day of filtration rates, the bigger filtration career was provided by the conduit media. On the other hand, for the 240 m³/m².day filtration rate, the bigger filtration career was provided by the gravel media. The gravel media spent less water to be cleaned in the filtration rates of 180 and 240 m³/m².day, and, for the 120 m³/m².day, the conduit media was the one that spent less water when washed. Therefore, one can conclude that the higher porosity can promote the treatment of higher volume of water, in the same filtration area, aiming at reducing the costs of na efficient water treatment technology, benefiting areas with lower financial means.